Influence of a nonionic surfactant on curcumin delivery of nanocellulose reinforced chitosan hydrogel - Sampath Udeni Gunathilake, Thennakoon M.; Ching, Yern Chee; Chuah, Cheng Hock; Illias, Hazlee Azil; Ching, Kuan Yong; Ramesh, Singh; Nai-Shang, Liou (Elsevier, 2018)
Nanocellulose reinforced chitosan hydrogel was synthesized using chemical crosslinking method for the delivery of curcumin which is a poorly water-soluble drug. Curcumin extracted from the dried rhizomes of Curcuma longa was incorporated to the hydrogel via in situ loading method. A nonionic surfactant (Tween 20) was incorporated into the hydrogel to improve the solubility of curcumin. After the gas foaming process, hydrogel showed large interconnected pore structures. The release studies in gastric medium showed that the cumulative release of curcumin increased from 0.21% ± 0.02% to 54.85% ± 0.77% with the increasing of Tween 20 concentration from 0% to 30% (w/v) after 7.5 h. However, the entrapment efficiency percentage decreased with the addition of Tween 20. The gas foamed hydrogel showed higher initial burst release within the first 120 min compared to hydrogel formed at atmospheric condition. The solubility of curcumin would increase to 3.014 ± 0.041 mg/mL when the Tween 20 concentration increased to 3.2% (w/v) in simulated gastric medium. UV–visible spectra revealed that the drug retained its chemical activity after in vitro release. From these findings, it is believed that the nonionic surfactant incorporated chitosan/nanocellulose hydrogel can provide a platform to overcome current problems associated with curcumin delivery.